The Role of the Relationship Between Fiscal Discipline and Exchange Rates in the Iraqi Economy (2004-2022) - Haqi Tomas (Journal of Economics, Assets, and Evaluation, 2025)
The relationship between the exchange rate and fiscal discipline is one of the most important lessons learned from economic theory, given the latter's effective role in saving monetary policy from chaos and lack of control. This relationship, according to international experiences, has had an effective impact on controlling most economic activities, whether in fiscal or monetary policy. Fiscal discipline has had an effective impact on achieving economic stability in many economies, especially those suffering from imbalances in the balance of payments. The Iraqi economy is one of the economies that is in real need of correcting the work of economic activities in line with the urgent need to make real changes at different levels. Through a theoretical review of the research, the researcher concluded that it is both easy and urgently necessary for economic policymakers to adopt fiscal protection and employ fiscal discipline to control the significant decline in the performance of fiscal policy, as demonstrated by the research findings. This can be achieved by expanding the types and quantities of public revenues to diversify them by stimulating dormant economic activities and introducing new types of products that can generate new revenue for the Iraqi economy. Introduction, Fiscal discipline is one of the most important indicators that has historically proven to have a direct and indirect impact on a wide range of economic variables, especially those whose effects are readily apparent in the economic reality. The exchange rate is one such variable, and maintaining it falls under the responsibility of the central bank. The exchange rate is a crucial factor in strengthening the monetary foundations of the Iraqi economy Some international experiences in neighboring countries have proven that it is possible to effectively use fiscal policy tools that have an actual impact on economic activity, which indicates a significant decline in the Iraqi economy, especially in the area of competition between economic activities at the level of fiscal and monetary policies. This research, relying on a group of modern sources whose authors adopted the topic of fiscal discipline, addresses the basic hypothesis of the research, which is that there is a positive relationship between the application of fiscal discipline and the achievement of economic stability through the tool of the exchange rate of the local currency against foreign currencies.